Model pembelajaran project based learning untuk meningkatkan kreativitas peserta didik pada materi menulis teks narasi kelas IV sekolah dasar - Siva Anisa Amalia; Retno Winarni (Didaktika Dwija Indria, 2025)
Writing is the final stage in language skills. One aspect that affects the writing ability of students is creativity. This study aims to describe the implementation of the Project Based Learning model to enhance the creativity of fourth-grade students in narrative text writing. This research is a classroom action research conducted in two cycles with four meetings. The subjects of this research are the teacher and the fourth-grade students of SDN Nayu B. The data in this study are both qualitative and quantitative. Data collection techniques include observation, interviews, tests, and documentation. Data validity testing uses source triangulation and technique triangulation. Data analysis is performed through data collection, data reduction, data presentation, and conclusions. The results of implementing the Project Based Learning model for teachers in cycles I and II were 78.90% and 92.70%. Meanwhile, for students in cycles I and II, the results were 74.21% and 88.80%. The assessment of creativity in this research used indicators of fluency, flexibility, originality, and elaboration, with results in cycles I and II of 78.81% and 91.66%, respectively. The conclusion of this research is that the application of the Project Based Learning model can enhance students' creativity in writing narrative texts.